Comprehensive analysis of archery performance: a case study - Jacquot, R.; Bouillet, K.; Mansour, K. B.; Jehl, J.-P.; Gauchard, G. (HAL Open Science, 2024)
Archery is an Olympic sport where archers aim at targets 70 meters away outdoors or 18 meters indoors, with the objective of achieving the highest score by hitting the center of the target. Callaway, Wiedlack, & Heller (2017) delineated archery shooting movements into seven phases. The aiming and the follow-through phases are particularly emphasized in the literature.Success in archery relies on strength and endurance of upper body muscles, stable posture, and strategic timing (Callaway et al., 2017; Zawi & Mohamed, 2013). Muscle activation patterns differ for the drawing and bow arms during the aiming and follow-through phases. Higher performance is associated with specific muscle activations, while others may hinder performance (Ertan, 2009; Simsek, Cerrah, Ertan, & Soylu, 2018). Postural stability, key in precision sports (Mononen, Konttinen, Viitasalo, & Era, 2006; Zawi & Mohamed, 2013), affects archery performance. Reduced movement speed of center of pressure (CoP) enhances accuracy during aiming (Sarro, Viana, & De Barros, 2021) and follow-through phases (Spratford & Campbell, 2017). Various temporal strategies have been identified, with shorter aiming phases correlated with higher performance (Sarro et al., 2021). Furthermore, individual archers employ distinct muscular and temporal strategies (Vendrame et al., 2022), underscoring the relevance of identifying performance determinants both individually and collectively. Therefore, the aim of this case study is to propose a precise and reproducible protocol to identify which performance determinants in archery are individual or common to all archers.